48. KNOWLEDGE SURVEY ON FOOT CARE IN DIABETIC PATIENTS UNDERGOING OUTPATIENT TREATMENT AT DONG MY CLINIC, THANH TRI, HA NOI IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge of foot care among outpatients with diabetes at Dong My clinic, Thanh Tri, Hanoi in 2024.Subjects and research methods: A descriptive case series study was conducted on 136 outpatients with diabetes at Dong My Clinic, Thanh Tri, Hanoi.Results: The average knowledge score was 14.53 ± 2.19, with only 0.7% of patients having poor  knowledge, 31.6% having average knowledge, and 67.6% having good knowledge.Conclusion: Providing systematic, well-organized, and regularly repeated education on foot care can improve patients’ knowledge, self-care behaviors, and adherence to treatment, thereby helping to prevent diabetic foot ulcers.
Keywords: type 2 diabetes; foot care knowledge.